The impact of the 1967 war on the creativity of Nizar Gabbani (Journal of Oriental Studies, 2016)
This article describes the views of syrian poet, Nizar Gabbani, on the Israeli-Palestinian confl ict which continues to be pressing up to now, the shocking impact of the six-day war on the Arab world in 1967 and radical criticism of the Arab dictatorship. His distinct style and specifi c way of poetic expression drew en ormous attention in the Arabic literature.